Implementation of Civil Servant Discipline Regulations Based on Government Regulation Number 94 of 2021 at the Civil Service Police Unit Office, Karawang Regency - Nova Desi Ratnasari; Yuniar Rahmatiar; Muhamad Abas; Suyono Sanjaya (Universitas Muhammadiyah Sumatera Utara, 2023)
Discipline of civil servants is the ability of civil servants to comply with obligations and avoid prohibitions specified in laws and regulations. According to Government Regulation Number 94 of 2021 concerning Discipline for Civil Servants which is the legal basis for regulating the formation of a good and correct state apparatus. Discipline must be upheld in an organization or agency, because without the support of good employee discipline, it is difficult for an agency to realize its goals. Problems with the discipline of Civil Servants, are currently receiving sharp attention from the public. The formulation of the problem in this research is how is the implementation process and efforts in carrying out and improving Civil Service Discipline Regulations based on Government Regulation Number 94 of 2021 at Satuan Polisi Pamong Praja Office, Karawang Regency. This type of research is Juridical Socialogis, data collection techniques were obtained through interviews, and data were analyzed qualitatively. The results of research by Satuan Polisi Pamong Praja Office of Karawang Regency apply preventive discipline to civil servants and efforts to increase employee discipline by disseminating regulations to employees as an effort to discipline employees